2001
DOI: 10.1016/s0584-8547(01)00324-x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and synchrotron radiation total-reflection X-ray fluorescence: new perspectives in detection limits and data analysis

Abstract: Having established detection limits for transition elements exceeding current requirements of the semiconductor industry, our recent efforts at the Stanford Synchrotron Radiation Laboratory (SSRL) have focused on the improvement of the detection sensitivity for light elements such as Al. Data analysis is particularly challenging for Al, due to the presence of the neighboring Si signal from the substrate. Detection limits can be significantly improved by tuning the excitation energy below the Si-K absorption ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In this case, as reported earlier, 6,14,15 the DL for Al is affected by the presence of the x-ray resonant Raman scattering ͑RRS͒ process in Si. Indeed, for photon beam energies tuned below the Si K-edge in order to avoid the strong K␣ fluorescence line, the x-ray RRS profile overlaps with the weak fluorescence line from Al impurities.…”
supporting
confidence: 68%
“…In this case, as reported earlier, 6,14,15 the DL for Al is affected by the presence of the x-ray resonant Raman scattering ͑RRS͒ process in Si. Indeed, for photon beam energies tuned below the Si K-edge in order to avoid the strong K␣ fluorescence line, the x-ray RRS profile overlaps with the weak fluorescence line from Al impurities.…”
supporting
confidence: 68%
“…Synchrotron radiation based X-ray fluorescence (SR-XRF) and total reflection X-ray fluorescence (SR-TXRF) techniques are the examples of such trends, where parts per trillion (ppt) level or, in absolute mass, femto gram detection sensitivities have been achieved. [22][23][24] Normally, XRF techniques are comparative in nature and type-standards are generally used to calibrate the spectrometers. Similarly, synthetic standards are employed to determine the DLs.…”
Section: Introductionmentioning
confidence: 99%
“…3(b) between the measured and fitted Ka 1,2 lines are probably due to this effect as a consequence of the finite beam energy resolution. The intensity excess found in the low-energy tails of the Ka 1,2 lines corresponds to the excitation of K-shell electrons into the M-shell and quasi-simultaneous filling of the 1s holes by L 2,3 electrons.…”
Section: Results and Interpretationmentioning
confidence: 92%
“…Several experiments [2,3] have shown that the detection limit of Al impurities on Si surface is limited by the presence of the X-ray resonant Raman scattering (RRS). For photon excitation energies tuned below the Si K-absorption edge to avoid the intense Si K fluorescence X-ray line, the RRS structure of Si is indeed overlapping with the Al K X-ray peak.…”
Section: Introductionmentioning
confidence: 99%